Rediscovering Our Heritage Linguistics - Suresh, C. (University of Jaffna, 2025)
In this presentation, I discuss how I experienced tensions between local and mainstream models of communication, linguistics, and teaching when I started teaching in the University of Jaffna in the mid 1980s. I introduce South Asian scholars who have theorized the differences and helped me resolve my tensions. I illustrate how my heritage linguistics now influences my language teaching, motivating a literacy and multilingual education that affirms students’ heritage languages and facilitates critical literacies and language proficiencies.